Solar PV powered‐sensorless BLDC motor driven water pump. Issue 3 (10th December 2018) - Kumar, Rajan; Singh, Bhim
Abstract : This study deals with a position sensorless brushless DC (BLDC) motor‐driven solar photovoltaic (PV) fed water pump. A technique based on the back electromotive force (back‐EMF) zero crossing is proposed for sensorless operation of the BLDC motor. The back‐EMF is derived from the difference of line voltages. Thus, a requirement of neutral potential is eliminated. In addition, the proposed drive avoids the use of phase current sensors. The speed is automatically adjusted according to the available peak power from the PV array. The devices of voltage source inverter, used to feed the BLDC motor pump, are switched at fundamental frequency. This leads to minimised switching losses. The responses of PV fed pumping system with the proposed drive are observed under various operating conditions. The suitability of the proposed topology is demonstrated through the hardware implementation.